Pengaruh Pembelajaran Play & Games dengan Mendengarkan Musik terhadap Perkembangan Keterampilan Gerak Dasar Motorik Anak - Dwi Anggareksa Setyo Widarto; Sugiharto Sugiharto; Supriyadi Supriyadi (Graduate School of Universitas Negeri Malang, 2021)
Abstract: Motor movement skills are an important aspect at every child's age and as an individual basis for reaching maturity in aspects of movement development. The research aims at an organized intervention program with various movement modifications through play and games activities. The design of this study was a pretest-posttest randomize control group design. Play and game learning activities for 30 minutes, by listening to music with a tempo of 140 beats/minute, with a frequency of twice/week for five weeks. data collection using TGMD-2 (Test Gross Motor Development-2). The results of statistical analysis with the Mann Whitney test determined an average score of 39.87 in the play and games experimental group without music and an average score of 47.37 for the play and games experimental group with music, there was a significant difference (2-tailed) 0.000 <0.05. This study shows that learning play and games by listening to music has a higher influence on the development of basic motor movement skills in grade II elementary school students.Abstrak: Keterampilan gerak motorik merupakan aspek penting pada setiap usia anak dan sebagai dasar individu untuk mencapai kematangan dalam aspek perkembangan gerak. Penelitian ini bertujuan untuk program intervensi yang terorganisir dengan berbagai modifikasi gerakan melalui aktivitas play and games. Rancangan penelitian ini adalah rancangan desain randomize control group pretest-posttest. Aktivitas pembelajaran play and game selama 30 menit, dengan mendengarkan musik bertempo 140 denyut/menit, dengan frekuensi dua kali/minggu selama lima minggu. Pengambilan data menggunakan TGMD-2 (Test Gross Motor Development-2). Hasil analisis statistik dengan uji mann whitney menunjukan skor rata-rata 39.87 kelompok eksperimen play and games tanpa musik dan skor rata-rata 47.37 kelompok eksperimen play and games dengan musik, terdapat perbedaan signifikan (2-tailed) 0.000 < 0.05. Penelitian ini menunjukkan pembelajaran play and games dengan mendengarkan musik yang memiliki pengaruh lebih tinggi terhadap perkembangan keterampilan gerak dasar motorik pada siswa kelas II sekolah dasar.